2018
DOI: 10.1002/app.46240
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerizable multifunctional monomers and their evaluation as reactive Bis‐GMA eluents

Abstract: Bis‐GMA {2,2‐bis[4‐(2′‐hydroxy‐3′‐methacryloyloxy‐propoxy)‐phenyl]‐propane}, TEGDMA <2‐{2‐[2‐(2‐methylprop‐2‐enoyloxy)ethoxy]ethoxy}ethyl‐2‐methylprop‐2‐enoate>, and methyl methacrylate (MMA) are some of the most commonly used monomers in the field of restorative dentistry. These compounds are characterized by having one or two terminal double bonds. Besides the effort to synthesize new monomers, several problems still affect the clinical behavior of contemporary dental materials. In this work, two monomers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Such techniques are able to detect the stretching vibration of carbon–carbon double bonds involved in the polymerization process . Recently, FTIR spectroscopy was used for the determination of the degree of double bond conversion of experimental dental composite resins based on these types of monomers. …”
Section: Introductionmentioning
confidence: 99%
“…Such techniques are able to detect the stretching vibration of carbon–carbon double bonds involved in the polymerization process . Recently, FTIR spectroscopy was used for the determination of the degree of double bond conversion of experimental dental composite resins based on these types of monomers. …”
Section: Introductionmentioning
confidence: 99%
“…The developed monomers showed many interesting mechanical and physical characteristics as summarized in Table 1 and the related chemical structure of the emerging diluent monomers are presented in Figure 2. These studies showed the enhanced properties of low volume shrinkage and shrinkage stress without compromising mechanical and biological properties to act as a viable candidate to replace TEGDMA, including aromatic methacrylates [60], triethylene glycol divinylbenzyl ether (TEG-DVBE) [61], diallyl(5-(hydroxymethyl)-1,3phenylene) decarbonate (HMFBA) and 5-(hydroxymethyl)-1,3-phenylene bis(2methylacrylate (HMFBM) [62], diallyl (propane-2,2-diylbis (1,4-phenylene)) biscarbonate (BPhADAC) [63], allyl(2-(2-(((allyloxy)carbonyl)oxy)benzoyl)-5-methoxyphenyl) carbonate (BZ-AL) [64], trifunctional monomers (5A1603DA, 5A13DMA) [65], and n-methyl-bis(ethylcarbamate-isoproply-α-methylstyryl)amine (Phene) [66]. Especially, a new hydrolytically stable monomer, TEG-DVBE, was suggested as a good alternative to design a longer-lasting dental resin composite in water-rich oral environments.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Also, the use of spiroorthocarbonate monomers [12], siloranes [13] and ormocers [14,15] has been incorporated into dental composite formulations to produce composites with less polymerization shrinkage. Also, our workgroup has been working among the last years in the synthesis an evaluation of allylic monomers for dental composites application [16][17][18][19][20][21], obtaining promising results.…”
Section: Introductionmentioning
confidence: 99%